The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1185/03007995.2011.644626
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan medoxomil combined with hydrochlorothiazide improves 24-hour blood pressure control in moderate-to-severe hypertension

Abstract: Study 1: EudraCT Number: 2006-003876-37; ClinicalTrials.gov identifier: NCT00430508; Study 2: EudraCT Number: 2006-003876-28; ClinicalTrials.gov identifier: NCT00430950.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…About 0.19% patients had serious adverse events and none were reported due to study drug (63). Fogari et al reported 3.9% of patients in an olmesartan/HCTZ 40/12.5 mg/day group had drug related adverse events compared to 0.7% in the olmesartan 40 mg/day monotherapy treatment arm.…”
Section: Safety and Tolerability Of Arbs In Hypertensionmentioning
confidence: 99%
“…About 0.19% patients had serious adverse events and none were reported due to study drug (63). Fogari et al reported 3.9% of patients in an olmesartan/HCTZ 40/12.5 mg/day group had drug related adverse events compared to 0.7% in the olmesartan 40 mg/day monotherapy treatment arm.…”
Section: Safety and Tolerability Of Arbs In Hypertensionmentioning
confidence: 99%